Functional and Probiotic Assessment of Lactic Acid Bacteria Derived from Commercial Milk Products - Swati Sharma,; Jayanand, (The Bioscan, 2025)
LAB is a large category of advantageous microorganisms that is broadly found in fermented dairy items, and has been studied extensively because of its probiotic and functional characteristics. The commercial products of milk (yogurt, cheese, kefir, and fermented milk drinks) are valuable sources of technologically valuable and health- promoting LAB strains. Over the last few decades, the growing consumer awareness concerning functional foods has led to greater research in the isolation and characterization of probiotic LAB obtained as commercial dairy matrices. The current review critically explores the diversity, isolation methods, functional aspects, probiotic assessment criteria, safety issues, molecular characterization methods, and applicability of technology of LAB obtained using commercial milk products. It focuses on gastrointestinal tolerance, antimicrobial action, adhesion, immunomodulatory, cholesterol-lowering, and antioxidant effects.